Investigative Study on Convective Heat Transfer inside Compartment during Fire Situation - Philippe Onguene Mvogo; Olivier Zatao Samedi; null Patrice Changement; Justin Tégawendé Zaida; Wolfgang Nzie; Henri Ekobena Fouda; Ruben Mouangue (Journal of Combustion)
According to the geometry of compartments, quantities of smokes released during fire tend to accumulate at ceiling so as to form a cloud of hot gases. Heat transfer between these hot gases and walls is decisive for the development of fire. An increase in temperature of these gases could lead to dangerous phenomena such as flashovers and backdrafts. Owing to experiments and numerical simulation, the objective of the present paper is to investigate on the influence of natural ventilation on convective heat transfer between hot gases and walls of a room in fire. So, varying the ventilation level, it was firstly about to carry out fire tests in an experimental room. Secondly, study was focused on the numerical simulation of these tests so as to estimate velocity field of burnt gases near walls during fire. Validation of numerical results has been done by confronting simulated results to experimental results. A full-scale extrapolation of results enabled revealing that while the ventilation level in the room changes, the amplitude of convective heat transfer changes according to the regime of fire. It was shown that for the fuel-controlled fire, the convective heat transfer coefficient strongly increases with the ventilation factor, and for the ventilation-controlled fire, convective heat transfer coefficient weakly decreases with the ventilation factor and remains nevertheless close to value  8.75W⋅m−2⋅K−1.